Outcome Evaluation of a Short-Term Hospitalization and Community Support Program for People Who Abuse Ketamine - Siu, Andrew M. H.; Ko, Flora S. L.; Mak, S. K. (Frontiers in Psychiatry, 2018)
Ketamine is a popular recreational drug among young people in Hong Kong. Long-term abuse of ketamine can lead to acute urological and medical issues, which often require immediate care at emergency rooms. Many patients require short-term hospitalization for medical management. This opens a brief time window, within which mental health professionals could engage young people who abuses ketamine in psychosocial, functional, and lifestyle interventions. The Crisis Accommodation Program (CAP) is a short-term hospitalization and community support program that addresses the health care needs of young people who abuse ketamine. During short-term hospitalization, the patient participates in a range of cognitive and psychosocial assessments, motivational interviewing, emotions management, and lifestyle re-design interventions. Upon discharge, social work professionals of non-government agencies continue to work with the patients on their action plans in the community. This evaluation study uses a quasi-experimental non-equivalent group design, in which the outcomes of the treatment group (n = 84) are compared with a comparison group (n = 34) who have a history of ketamine abuse but who have not joined the treatment program. The results confirm that the treatment group showed significant increases in motivation for treatment, reduction in drug use, improvement in cognitive screening tests, healthy lifestyle scores, and self-efficacy in avoidance of drugs over 13 weeks. When compared with the comparison group, the treatment group had significant decreases in anxiety and treatment needs and had moved from pre-contemplation to the contemplation or preparation stage. However, there were no significant changes in outcome measures covering lifestyle or self-efficacy in drug avoidance. Overall, the CAP is effective in reducing drug use, anxiety, and helping clients to move from pre-contemplation to the contemplation or preparation stage of change. The study results suggest that health care professionals can successfully engage young people who abuse ketamine to participate in a package of psychosocial interventions, motivational interviewing, and lifestyle re-design during their hospital stay for management of urological problems. The CAP also highlights the importance of collaboration between hospitals and community social services in the management of addiction.